The social net in families with newborn infants at risk during the first year of life: prospective study - Marques, Fernanda Baptista; Teston, Elen Ferraz; Barreto, Mayckel da Silva; Furlan, Mara Cristina Ribeiro; Marcon, Sonia Silva (Online Brazilian Journal of Nursing, 2010)
Introduction: A birth of a child that presents some survival risk, demands from parents and family a series of adjustment mechanisms in order to face and incorporate that new situation into their lives. Objective: Identify the resources and the social net used by the families of a newborn infant at risk in the quotidian, and in the presence of health problems. Method: A prospective descriptive-exploratory study of the cohort type, accomplished with 238 children born in the municipal district of Maringá-PR who were included in the Program of Surveillance of Newborn Infants at Risk. Six home visits were accomplished, when the mothers were interviewed through a mixed type questionnaire, containing questions regarding family, mother and child. The information was inserted in a database for obtaining simple frequency. Results: Mother alone or with the help of a companion and of some relatives, is the main caretaker of the newborn infant at risk. However, the grandmother’s participation increases as the child grows, due to the mothers' need of going back to work. The Family Health Strategy program was mentioned as support net by 65.4% of the families. Nevertheless, more than half of the children were not visited by the FHS and the number of visits decreased as the children grew. Implications for Nursing: The health professionals need to understand their role as support net to the families. Certainly, this will determine more commitment and involvement in relation to the follow-up on the growth and development of the child, as well as give instruments to the family, especially to the mother, to take a better care of the baby.